Studi Polimerisasi Ester Dari Asam Lemak Sawit Distilat (ALSD) Menggunakan Inisiator Benzoil Peroksida 0,1 % - Dwifirman, Widya; Zultiniar, Zultiniar; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Polyesters are polymers which contain the ester functional group in their main chain. In this research, used raw materias were Palm Fatty Acid Distillate (PFAD) and methanol. PFAD as a byproduct of the processed of palm oil has great potential to be used as raw material for polyester products. The purpose of this research was study polymerization of ester from Palm Fatty Acid Distillate (PFAD) using initiator of benzoyl peroxide 0,1%. There are two steps in this research, esterification reaction in the presence of sulfuric acid and the polymerization reaction with the help of benzoyl peroxide as initiator. Fixed variable used is the reactant composition of 1:8, speed of stirred 150 Rpm, composition of H2SO4 1% (w/w) PFAD and composition of benzoyl peroxide 0,1% (w/w) of methyl ester, while changed variable is the polymerization reaction time 3, 4 and 5 hours and polymerization reaction temperatures of 120, 130 and 140Â° C. Results of research on the esterification stage is obtained methyl ester with density 0,779 g/ml, viscosity 0,03746 cp and GC-MS analysis showed that the purity of methyl esters is 88,9%. GC-MS analysis sample after polymerization reaction showed that purity of methyl ester is 3,47%.Keywords : esterification, methyl ester, pfad, polymerization